Determining Public Provision of Education Services in a Sequential Education Process - Romero, J (Walter de Gruyter GmbH, 2012)
This paper applies a political economy approach to the study of the endogenous determination of the size and composition of a public education budget. In this model, there are two education stages: the first is compulsory, while advanced education is optional. Parents decide on the education policy by a majority vote, children attend schools and then decide whether to get advanced education. This paper shows that even in a simple scenario where only public education is available, children s college-attendance decisions may lead the single-crossing condition to fail, which indicates that a majority voting equilibrium may not exist. In a scenario where individuals can opt for private education services, the model provides necessary and sufficient conditions for an equilibrium of the "ends-against-the-middle" type, where the poor are decisive. An implication of this result is that the opting-out feature of education may improve the welfare of the poor. Copyright © 2012 De Gruyter. All rights reserved.
Keywords: compulsory education; advanced education; majority vote